Transient parameters of a coated quartz crystal microbalance sensor for the detection of volatile organic compounds (VOCs) - Shafiqul Islam, A. K M; Zhari, Ismail; M. Nizam, Ahmad; Bahruddin, Saad; Abdul Rahman, Othman; Ali Yeon, Md Shakaff; Abdul Razak, Daud; Ishak, Z. (Elsevier B.V., 2009)
Link to publisher's homepage at www.elsevier.com